EFFECTIVENESS OF TREATING OF Pinus halepensis Mill. SEEDS WITH ELECTRIC SHOCK AND PERIODS AND GIBBERELLIC ACID IN CHANGES OF METABOLIC SOME THE PHYSIOLOGICAL PROCESSES OF SEEDLINGS - Sabah Shareef; Mudhafar O. Abdullah; Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
The results of the chemical analysis showed that the values ​​of each of the leaves content of the Pinus halepensis Mill. seedlings of the total proteins , chlorophyll have increased significantly with increasing the power of electrocution at 4 and 6 amp. Also each of leaves content of the total phenols and potassium increased at 6 amp power of electrocution. So, one can note that all periods of electrocution caused a significant outweigh in all the investigated chemical characteristics in comparison to control treatment except for attribute of the leaves content of potassium. The obtained results indicate treating seeds with Gibberellic acid led to a significant increase in all the chemical characteristics of seedlings compared to the comparative treatment except seedling leaf content of the total chlorophyll.